Context-based patient choice management in healthcare. Issue 1 (12th February 2018) - Chen, An; Lillrank, Paul Martin; Tenhunen, Henni; Peltokorpi, Antti; Torkki, Paulus; Heinonen, Seppo; Stefanovic, Vedran
Abstract : Purpose: In healthcare, there is limited knowledge of and experience with patient choice management. The purpose of this paper is to focus on patient choice, apply and test demand-supply-based operating (DSO) logic integrated with clinical setting in clarifying choice contexts, investigate patient's choice-making at different contexts and suggest context-based choice architectures to manage and develop patient choice. Design/methodology/approach: Prenatal screening and testing in the Helsinki and Uusimaa Hospital District (HUS), Finland, was taken as an example. Choice points were contextualized by using the DSO framework. Women's reflections, behaviors and experience at different choice contexts were studied by interviewing women participating in prenatal screening and testing. Semi-structured interview data were processed by thematic analysis. Findings: By applying DSO logic, four choice contexts (prevention, cure, electives and continuous care) were relevant in the prenatal screening and testing episode. Women had different choice-making in prevention and cure mode contexts regarding choice activeness, information needs, social influence, preferences, emotion status and choice-making difficulty. Default choice was widely accepted by women in prevention mode and individual counseling can help women make informed choice in cure mode. Originality/value: The authors apply the DSO model to contextualize the patient choice in one care episode and compare patient choice-making at different contexts. The authors also suggest the possible context-based choice architectures to manage and promote patient choice